Severe Microcytic Anaemia due to Chrohn's Disease - An Uncommon Presentation (Bangladesh Journal of Medicine, 2013)
Crohns disease is an uncommon disease. Most common presentation is abdominal pain, diarrhea and weight loss. It may present as subacute or even acute intestinal obstruction. Crohns disease is very rare in Bangladesh. Here we report a case of Crohns disease where the initial presentation was severe microcytic hypochromic anaemia. Who had repeated blood transfusion for one year. Initially cause was not detected. Later on he presented with subacute intestinal obstruction. After all diagnostic work up no definitive diagnosis could be found. So laparotomy was done in Bangabandhu Shiekh Mujib Medical University (BSMMU). Histopathology report was suggestive of Crohns disease and he was on mesalazine with significant clinical improvement. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13620 Bangladesh J Medicine 2010; 21: 101-104